Complete genome sequence of a vaccinal Newcastle disease virus strain isolated from an owl (Rhinoptynx clamator) - Van Borm, Steven; Rizotto, Laï¿½s S.; Ullmann, Leila S. [UNESP]; Scagion, Guilherme P.; Malossi, Camila D. [UNESP]; Simï¿½o, Raphael M.; Araï¿½jo, Joï¿½o P. [UNESP]; Cordeiro, Izabelle M.; Keid, Lara B.; Oliveira, Trï¿½cia Maria F. Sousa; Soares, Rodrigo M.; Martini, Matheus C.; et al. (American Society for Microbiology, 2016)
A Newcastle disease virus (NDV) was isolated in chicken embryonated eggs after detection by real-time reverse transcription- PCR (RRT-PCR) from a captive owl swab. The complete genome sequence of APMV-1/Rhinoptynx clamator/Brazil/22516/2009 (APMV-1, avian paramyxovirus type 1) was obtained using Illumina sequencing. Phylogenetic analysis of the complete genome classified the isolate within NDV class II genotype II.